Effect of a new incision management system (PREVENA®) on wound healing after endophlebectomy of the common femoral vein: a case series. (December 2016) - Gombert, A.; Barbati, M.; Wittens, C.; Grommes, J.; Jalaie, H.
Abstract Background New endovascular techniques facilitate treatment of complex deep vein obstructions in cases of post-thrombotic syndrome. In a relevant number of these patients, endophlebectomy including the implantation of an arteriovenous fistula between the common femoral artery and the femoral vein is indispensable in order to establish a good inflow. These procedures display a high risk of wound complications. Despite conservative efforts to prevent these postoperative complications, wound healing problems occur in more than 20 % of cases. The present case report is the first description of wound dressing using a PREVENA® incision management system in cases of endophlebectomy. Case presentation A single center's experience with the incision management system PREVENA®, which was used after endophlebectomy and venous stenting in complex hybrid procedures in three white men aged 46 years, 53 years, and 61 years is the subject of this case report. Although the surgical procedures were performed under therapeutical anticoagulation and took a couple of hours, no wound complications occurred. Conclusions These encouraging results underline a potential benefit of the incision management system PREVENA® in cases of complex venous recanalization including endophlebectomy of the femoral vein as well as the implantation of an arteriovenous fistula.